PENGARUH MODEL PjBL BERBANTUAN WORDWALL TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PEMBELAJARAN IPAS KELAS IV MI - Yulia Aufa; Khairiani Idris; Sarah Fazilla (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the Project-Based Learning (PjBL) model, supported by the Wordwall platform, on students’ creative thinking skills in science education regarding grafting in fourth-grade elementary school. This quantitative study employed a quasi-experimental method using a nonequivalent control group design. Data collection was conducted through pretests and posttests in two groups: the experimental class (PjBL and Wordwall intervention) and the control class (conventional method). The measurement of creative thinking skills was based on four main indicators, namely fluency, flexibility, originality, and elaboration. Analysis results indicate a significant difference in achievement between the two groups. The average posttest scores of the experimental class were found to be superior to those of the control class. Additionally, the creativity profiles of students in the experimental class showed a significant increase toward the “creative” and “highly creative” categories. It is concluded that the implementation of PjBL supported by Wordwall has a positive and significant impact on enhancing students’ creative thinking skills. Consequently, this model is highly recommended as an innovative learning strategy to optimize student engagement and higher-order thinking skills in elementary schools.